2012
DOI: 10.1080/10503307.2012.692214
|View full text |Cite
|
Sign up to set email alerts
|

Existential dynamic therapy (“VITA”) for treatment-resistant depression with Cluster C disorder: Matched comparison to treatment as usual

Abstract: Existential suffering may contribute to treatment-resistant depression. The "VITA" treatment model was designed for such patients with long-standing depression accompanied by existential and/or religious concerns. This naturalistic effectiveness study compared the VITA model (n = 50) with a "treatment as usual" comparison group (TAU; n = 50) of patients with treatment-resistant depression and cluster c comorbidity. The TAU patients were matched on several characteristics with the VITA patients. The VITA model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…First of all, to our knowledge, this is the first study to demonstrate that high-intensity residential treatment produce marked changes at the level of observer-based diagnostic assessments. We believe this to be an important addition to the existing literature validating and consolidating findings from previous studies (2,8,9,11,12).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…First of all, to our knowledge, this is the first study to demonstrate that high-intensity residential treatment produce marked changes at the level of observer-based diagnostic assessments. We believe this to be an important addition to the existing literature validating and consolidating findings from previous studies (2,8,9,11,12).…”
Section: Discussionsupporting
confidence: 79%
“…There are also recent studies indicating that high-intensity and relatively short-term residential treatment may be highly effective for treatment-resistant populations. For example, Stålseth et al (8) and Solbakken and Abbass (2,9,10) have shown that intensive time-limited, residential treatments are effective in helping a large proportion of patients with known treatment-resistant depressive- and anxiety disorders. Stålseth et al demonstrated that a tailored psychodynamic existential 12-week treatment programme for patients with treatment-resistant depression and comorbid Cluster C personality disorder was superior to residential treatment as usual (TAU) of identical length with matched controls.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by findings from two previous studies on similar populations. 4,5 Interestingly, improvement happened within 8 weeks, indicating that highly intensive residential treatment may not only increase effectiveness of treatment efforts, but may also produce an increase in the swiftness of improvement as compared with standard out-patient psychotherapy. 2 These findings suggest substantial implications for the delivery of mental health care.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the program improved both interpersonally and symptomatically, and also significantly outperformed a group of matched controls receiving residential treatment as usual. 4 Furthermore, a 6-month residential program using an intensive short-term dynamic psychotherapy (ISTDP) approach in the Netherlands has demonstrated large and sustained therapeutic effects with treatment-resistant, personality disordered patients. 5 These studies provide some evidence that tailored residential treatment programs may be helpful for patients with treatment-resistant disorders.…”
mentioning
confidence: 99%
“…The importance of psychologically addressing religious struggles was further emphasized based on psychologists' professional competences and ethical responsibility (Gonsiorek et al 2009). Addressing existential and religious issues in psychotherapy indicated a possible benefit for mental health (Viftrup et al 2016;Stålsett et al 2012;Gebler and Maercker 2014). However, the therapeutic approaches and methods used were often specific in ways that challenged their generalizability to the methods applied by psychologists without this specific existential or theological knowledge and training.…”
Section: Introductionmentioning
confidence: 99%